Use of Stingless Bee Honey (Trigona Itama) as A Wound Dresses for Patients With Diabetic Foot Ulcers: A Literature Review - Aziz Mulim, Dede Nur; Mohd Said, Faridah Binti; Nambiar, Nisha; Dirgahayu, Inggrid; Sarinengsih, Yuyun (Advances In Social Humanities Research, 2024)
Diabetic foot ulcers often cause severe complications such as infection and lower extremity amputation. To prevent death, comprehensive interventions combined with CAM are needed. Studies have been well done on this topic; However , we rarely discuss the benefits of stingless bee honey ( Trigona Itama ) for diabetic foot ulcers. Therefore, this study intends to evaluate the use of Stingless Bee Honey ( Trigona Itama ) before implementation in human subjects. A literature review search was conducted to achieve the research objectives. Several online databases are involved in research assessment. The search criteria were determined by considering the topic, research design, type of article, and year of publication. The findings show that Stingless Bee Honey ( Trigona Itama ) has the potential for diabetic foot ulcers for a certain period. Future studies should focus on the long-term results of this honey when used in patients with chronic wounds.